Deposition and optimization of nanoparticulate manganese dioxide thin films for electrochemical applications - Awangku Nabil Syafiq, Awangku Metosen (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The deposition and optimization of nanoparticulate manganese dioxide (MnO2) thin films as electrode material for the fabrication of electrochemical capacitors have received increasing attention among researchers worldwide. Among major issues that need to be addressed include, microstructural optimization of MnO2 thin films in order to enhance their specific capacitance, and the development of efficient and effective approaches for the fabrication of MnO2 thin film electrochemical capacitors. In this study, we have investigated the influence of deposition parameters such as MnO2 sol pH, sol concentration and addition of different type of surfactants using the self-assembly horizontal submersion approach. The surface morphologies and microstructure of MnO2 thin films were optimized by varying these deposition parameters. The electrochemical properties of MnO2 thin films were enhanced through microstructural control of nanoparticulate thin films deposited on electrically conductive supporting substrate. Besides nickel sputtered polyethylene terephthalate (PET) substrate, conductive layers of CuS and nickel were deposited sequentially on PET by chemical bath deposition and electrodeposition processes. Nanoparticulate MnO2 thin film was subsequently deposited on the conductive Ni/CuS/PET supporting substrate. Nanostructured multilayer MnO2/Ni/CuS composite films on PET supporting substrate exhibited satisfactory capacitive behaviors in mild aqueous Na2SO4 electrolyte. In addition, nanoparticulate MnO2 thin films were deposited on nickel sputtered PET substrates using the electrophoretic deposition (EPD) process. Deposition parameters such as deposition potential, deposition duration and addition of dispersant agents were optimized to enhance the electrochemical properties of MnO2 thin films. The capacitive behaviors of nanoparticulate MnO2 thin films deposited on both Ni/CuS coated and nickel sputtered PET iii supporting substrates were evaluated as electrode materials for the fabrication of thin film electrochemical capacitors.